Dynamic features of plasma plume and molten pool in laser lap welding based on image monitoring and processing techniques. (January 2019) - Meng, Wei; Yin, Xiaohui; Fang, Junfei; Guo, Lijie; Ma, Qunshuang; Li, Zhuguo
Highlights: Plasma and molten pool instantaneous images in different gap were observed. The dynamic features of plasma and melt pool were extracted. The time domain and frequency field of plume and molten pool were calculated. A novel monitoring method for gap was obtained. Abstract: Laser lap welding is the typical welding mode for laser-welded steel sandwich constructions, and the welding quality is a critical point for their comprehensive performance. However, the special welding mode for the sandwich plate proposes challenges attributed to the gap between upper plate and below plate are difficult to be avoided and so real-time monitoring of gap is very important in laser welding. On the basis of the plume and molten pool images captured by two high-speed cameras, the characteristics of instantaneous plasma plume and molten pool were calculated, and their process parameters were extracted statistically in time domain and frequency field. After preprocessing the images, the quantification of the plume and molten pool was performed. Using static and dynamic features of plume and molten pool, the effect of gap on the welding procedure was discussed for laser lap welding. The results revealed that the gap was closely related to the dynamic variation of plasma plume and molten pool. The dynamic features of plume and molten pool could be better reflected by the plume area, peak frequency and molten pool length in different gap. The monitoring method based on the synthetic characteristics of vapor plume and molten pool was convenient, effective and promising in production.